Reporting on the opioid crisis (2000-2018): role of The Globe and Mail, a Canadian English-language newspaper in influencing public opinion - Amanda My Linh Quan; Lindsay A. Wilson; Salima S. Mithani; David T. Zhu; A. Brianne Bota; Kumanan Wilson (BMC, 2020)
Abstract Background We aim to describe the general characteristics of how the Canadian newspaper The Globe and Mail reports on opioid-related news, the opioid crisis and its victims, and explore how Canadians' perceptions of the opioid crisis could have developed over time from this reporting. The Globe and Mail has the highest circulation among Canadian newspapers and is Canada's newspaper of record. Methods Reviewers performed independent, blinded bibliometric searches of all The Globe and Mail articles archived in the Canadian Periodicals Index Quarterly spanning an 18-year period (1 January 2000-1 June 2018) related to the keywords "opioids" or "drugs and opioids" and "opiates". Independently and in duplicate, reviewers manually extracted qualitative data from articles and identified emergent themes. Articles were screened independently by both reviewers based on the inclusion criteria. Conflicts were resolved by discussion and consensus. Social representation theory was used as a framework for describing how the opioid crisis is portrayed in Canada. Results Our search yielded 650 relevant opioid articles. The number of articles peaked in 2009, 2012, and in 2016, coinciding with major developments in the epidemic. The language used in this discourse has evolved over the years and has slowly shifted towards less stigmatizing language. Content analysis of the articles revealed common social representations attributing responsibility to pharmaceutical companies, physicians, and foreign countries. Conclusions The Globe and Mail's coverage of the opioid crisis is focused on basic social representations and attributed responsibility for the crisis to a few collectives. A shift toward coverage of the root causes of the opioid epidemic could positively influence the general public's perception of the opioid crisis and promote deeper understanding of the issue. Journalists face several obstacles to achieve greater focus and framing of the opioid crisis; a closer working relationship between the media and the research community is needed.